Uji Efektivitas Sediaan Sintetis Dan Herbal Terhadap Percepatan Penyembuhan Luka Bakar Derajat II Pada Tikus Putih Jantan - Vania Zahara; Helmice Afriyeni; Rosiana Rizal (Jurnal Sains Farmasi Dan Kesehatan, 2023)
Burns are injuries that are caused by direct contact with heat, chemicals, electricity and radiation that cause tissue, muscle, nerve skin damage and tearing of blood vessels to disrupt the body's balance. The purpose of this study was to determine the effect of preparation and time on the reduction of burn area in male white rats. All rats were induced by burns and divided into 5 groups, namely the bioplacenton preparation group, synergy herbal oil, aloevera medigel, then treated with the preparation for 28 days. Wound area measurements were carried out on days 0, 4, 8, 12, 16, 20, 24 and 28, then histopathological examination of the rat skin tissue was carried out on the final day. The data from the study measuring the area of ​​the wound were analyzed using the Two-Way Anova method followed by Duncan's, then quantitative descriptive histopathology using the Kruskal Wallis method. The results of statistical analysis of preparation and time had a significant effect on decreasing burn area in male white rats (<0.05). The dosage and time groups have effectiveness in reducing wound area, where the percentage of the largest decrease in wound area is in the herbal preparation of Medigel aloevera and the longer the time of administration of the preparation the greater the percentage decrease in wound area. In addition, the histopathological state of rat skin tissue at the end of the day for all groups was in a mature state in epithelial cells and 6-10 blood vessel cells with score 2.